2009
DOI: 10.1007/s10886-009-9658-9
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Herbivores are not Deterred by Brevetoxins Produced by the Red Tide Dinoflagellate Karenia Brevis

Abstract: Gulf of Mexico blooms of the dinoflagellate Karenia brevis produce neurotoxic cyclic polyethers called brevetoxins. During and after a red tide bloom in southwestern Florida, K. brevis cells lyse and release brevetoxins, which then sink to the benthos and coat the surfaces of seagrasses and their epiphytes. We tested the possibility that these brevetoxin-laden foods alter the feeding behavior and fitness of a common benthic herbivore within Floridean seagrass beds, the amphipod Ampithoe longimana. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Although there is more research recently on the effects of toxins produced by pelagic microalgae on the invertebrate microbenthos, this remains a relatively poorly researched area. Sotka et al (2009) reported that, after a red tide bloom, the brevetoxin-producing red tide dinoflagellate Karenia brevis [(Davis) G.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is more research recently on the effects of toxins produced by pelagic microalgae on the invertebrate microbenthos, this remains a relatively poorly researched area. Sotka et al (2009) reported that, after a red tide bloom, the brevetoxin-producing red tide dinoflagellate Karenia brevis [(Davis) G.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that dinoflagellates are a nutritional food source for marine copepods and conducive to their growth and development. In the case of the dinoflagellate P. Micans, the toxins secreted by could potentially cause a problem (Koski et al, 2008;Sotka et al, 2009;Zheng, 2011). Additionally, among the five microalgae species, I. galbana, N. closterium f. minutissima, and P. micans are suspended in the water column as single cells, while the two diatoms, C. muelleri and S. costatum, normally form chains of multiple cells.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates natural settlement of K. brevis cells, coating/adsorption of benthic food sources by brevetoxins released by lysed K. brevis cells, and/or possible deposition of zooplankton (e.g., copepod) fecal pellets containing undigested dinoflagellates (Maneiro et al, 2000). The crustacean amphipods, Ampithoe longimana and A. valida, common herbivores in Florida seagrass beds and an important food source for juvenile fish, readily ingested and accumulated brevetoxins from their own food (freeze-dried seaweed) experimentally coated with K. brevis extracts or purified brevetoxins (Sotka et al, 2009). Benthic crustaceans (the barnacle, Balanus eburneus and mud crab Eurypanopeus depressus) were found to be relatively resistant to the effects of brevetoxins even when exposed to lysed K. brevis cells (Sievers, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Motile invertebrate mesograzers such as copepods, isopods, and amphipods live several months and are primary grazers of seagrass epiphytes (Jernakoff et al, 1996). Amphipods are relatively resistant to brevetoxin toxicity (Sotka et al, 2009) and could likely serve as a vector transferring toxins in seagrass communities. In addition, some mobile filter feeders like the wing oyster Pinctada imbricata , can detach from senescing seagrass blades and reattach to living blades in the canopy (J. Fourqurean, personal observations), providing another potential vector.…”
Section: Discussionmentioning
confidence: 99%